Assessment of CD4+ T cell recovery after direct-acting antiviral hepatitis C treatment in HIV/HCV coinfected immunological nonresponders to ART - Violetta Vlasova; Evgeniya Saidakova; Larisa Korolevskaya; Nadezhda Shmagel; Konstantin Shmagel (Exploration of Medicine)
Aim: This study investigated the effects of successful hepatitis C virus (HCV) treatment with direct-acting antivirals (DAAs) on CD4+ T cell recovery in HIV/HCV coinfected immunological non-responders (INRs) to antiretroviral therapy (ART). The study assessed changes in CD4+ and CD8+ T cell counts, immune activation, inflammation, T cell exhaustion, and the size of the naïve CD4+ T cell pool following DAA therapy to determine whether HCV suppression enhances immune restoration in coinfected INRs. Methods: Three groups were analyzed: DAA-treated INRs (n = 9), untreated HIV/HCV coinfected INRs (n = 10), and healthy controls (n = 10). Plasma cytokine levels and viral loads were quantified using multiplex immunoassay and real-time PCR. Peripheral blood mononuclear cells were analyzed via flow cytometry to evaluate T cell subsets, activation (HLA-DR+CD38+), and exhaustion markers (PD-1, TIGIT). Results: Both INR groups showed significantly lower CD4+ T cell counts and elevated CD4+ T cell proliferation compared to controls, with no significant difference between DAA-treated and untreated patients. Deficits in naïve CD4+ T cells were observed in both INR groups but reached statistical significance only in untreated individuals. Activated CD4+ and CD8+ T cells and proinflammatory cytokines of IFN and IL-10 families remained elevated in INRs after DAA treatment. DAAs reduced PD-1 and TIGIT expression on CD4+ T cells, suggesting attenuated exhaustion, but did not alter exhausted T cell frequencies in CD4+ or CD8+ T cells. Conclusions: HCV coinfection in people living with HIV (PLWH) not only increases the risk of immunological non-response to ART but also has lasting impacts on the immune system. Even after successful HCV clearance with DAAs, INRs experience persistent immune dysregulation, including low CD4+ T cell counts, deficits in the naïve CD4+ T cell compartment, and ongoing inflammation. This indicates that HCV eradication alone is insufficient to reverse the long-term immune damage resulting from coinfection.